2015
DOI: 10.1039/c5dt02557e
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide mixed-ligand complexes of the [Ln(CAPh)3(Phen)] and [LaxEu1−x(CAPh)3(Phen)] (CAPh = carbacylamidophosphate) type. A comparative study of their spectral properties

Abstract: A series of complexes Ln(Pip)3(Phen) (Ln(iii) = La, Ce-Nd, Sm-Lu, Y; HPip (CAPh type ligand) = 2,2,2-trichloro-N-(dipiperidin-1-yl-phosphoryl)acetamide, Phen = 1,10-phenanthroline) has been synthesized. The lanthanum(iii) doped europium(iii) complexes ([LaxEu1-x(Pip)3(Phen)], x = 0.99, 0.95, 0.50) have been obtained by the co-crystallization method. The complexes have been characterized by means of X-ray diffraction, IR, (1)H and (31)P-NMR and absorption spectroscopy. Emission and excitation luminescence spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 70 publications
1
8
1
Order By: Relevance
“…7 F 2 Eu 3 + transition was observedi n[ Eu(pip) 3 (phen)] when compared to lanthanum-doped europiumc ompounds. [67] Furthermore,e mission intensity enhancement was induced by symmetry lowering in heterometallic TbÀPt complex ([Tb 2 Pt 3 (SAc) 12 (H 2 O) 2 ]). [68] In contrast to these studies, the here observed polymorph-specific spectralf eatureso f1-3 cannot be ascribed to the introduction of guest ions or external forces, thus their origin must be related to the complexes' intrinsic crystal structures.…”
Section: Opticalproperties:e Mission Spectroscopymentioning
confidence: 99%
“…7 F 2 Eu 3 + transition was observedi n[ Eu(pip) 3 (phen)] when compared to lanthanum-doped europiumc ompounds. [67] Furthermore,e mission intensity enhancement was induced by symmetry lowering in heterometallic TbÀPt complex ([Tb 2 Pt 3 (SAc) 12 (H 2 O) 2 ]). [68] In contrast to these studies, the here observed polymorph-specific spectralf eatureso f1-3 cannot be ascribed to the introduction of guest ions or external forces, thus their origin must be related to the complexes' intrinsic crystal structures.…”
Section: Opticalproperties:e Mission Spectroscopymentioning
confidence: 99%
“…The mean average of all La-O bond lengths is 2.476 Å . The La-N distances are with 2.699 (3) and 2.700 (3) Å (mean value 2.693 Å ) shorter than those previously obtained for a 1,10-phenanthrolinate lanthanum (III) complex with hexafluoroacetylacetonate (2.747-2.782 Å ; Rogachev et al, 2005) and longer than La-N bonds in a carbacylamidophosphate ligand complex (2.601-2.635 Å ; Litsis et al, 2015;Sokolnicki et al, 1999).…”
Section: Structural Commentarymentioning
confidence: 64%
“…The set of the angles between pairs of the faces intersecting along the type b edges (shown in Fig. 2) allows us to assign a distorted bicapped trigonal-prismatic environment ( 1 = 9.48 , 2 = 18.48 , 3 = 43.57 , 4 = 44.89 , ' 1 = 12.47 , ' 2 = 16.05 ) similar to that of the Tb(Pip) 3 (Phen) mixed-ligand complex with 2,2,2-trichloro-N-(dipiperidin-1-ylphosphoryl)acetamide, HPip (Litsis et al, 2015).…”
Section: Structural Commentarymentioning
confidence: 99%
“…Oscillator strength values P( Â 10 8 ) of hypersensitive 4 I 9/2 -4 G 5/2 , 2 G 7/2 transition for Nd1, Nd2 and related Nd III complexes [11,12]. and at 345 nm (for Eu2).…”
Section: Tablementioning
confidence: 99%